Clinical Use of Cerebrovascular Compliance Imaging to Evaluate Revascularization in Patients With Moyamoya - Watchmaker, Jennifer M (Neurosurgery, 2019)
BACKGROUND: Surgical revascularization is often performed in patients with moyamoya, however routine tools for efficacy evaluation are underdeveloped. The gold standard is digital subtraction angiography (DSA); however, DSA requires ionizing radiation and procedural risk, and therefore is suboptimal for routine surveillance of parenchymal health. OBJECTIVE: To determine whether parenchymal vascular compliance measures, obtained noninvasively using magnetic resonance imaging (MRI), provide surrogates to revascularization success by comparing measures with DSA before and after surgical revascularization. METHODS: Twenty surgical hemispheres with DSA and MRI performed before and after revascularization were evaluated. Cerebrovascular reactivity (CVR)-weighted images were acquired using hypercapnic 3-Tesla gradient echo blood oxygenation level-dependent MRI. Standard and novel analysis algorithms were applied (i) to quantify relative CVR (rCVR(RAW)), and decompose this response into (ii) relative maximum CVR (rCVR(MAX)) and (iii) a surrogate measure of the time for parenchyma to respond maximally to the stimulus, CVR(DELAY). Measures between time points in patients with good and poor surgical outcomes based on DSA-visualized neoangiogenesis were contrasted (signed-rank test; significance: 2-sided P < .050). RESULTS: rCVR(RAW) increases (P = .010) and CVR(DELAY) decreases (P = .001) were observed pre- vs post-revascularization in hemispheres with DSA-confirmed collateral formation; no difference was found pre- vs post-revascularization in hemispheres with poor revascularization. No significant change in rCVR(MAX) post-revascularization was observed in either group, or between any of the MRI measures, in the nonsurgical hemisphere. CONCLUSION: Improvement in parenchymal compliance measures post-revascularization, primarily attributed to reductions in microvascular response time, is concurrent with collateral formation visualized on DSA, and may be useful for longitudinal monitoring of surgical outcomes.